Accelerating and scaling up Africa’s climate change adaptation and mitigation actions: Experiences and lessons learned - Majaliwa, Mwanjololo J.G.; Nakayiwa, Florence; Waswa, Moses; Ekepu, David (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
As part of the 19th Annual General Meeting (AGM) of the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM), held on 28th October-2nd November 2023 at Palais des Congres in Yaounde, Cameroon, partners of AICCRA (Accelerating Impacts of CGIAR Climate Research for Africa) RUFORUM and WASCAL have organized a side event entitled “Accelerating and scaling up Africa’s climate change adaptation and mitigation actions”. The overall objective of the side event was to share lessons and experiences as well as address challenges in accelerating and scaling up Africa’s climate change adaptation and mitigation actions. Specifically, the side event aims to share lessons learned from climate change mitigation research on the continent; increase awareness of CSA/CIS technologies, practices, and innovations developed by the AICCRA Project among university stakeholders, and disseminate completed training modules developed by RUFORUM and WASCAL for integration into university curricula. The side event was attended by 42 people, including 8 women, from Ouganda, Kenya, Zambia, Zimbabwe, Malawi, Ghana, Ivory Coast, Ethiopia, Cameroon, Democratic Republic of Congo, Benin, Mali, Malawi, Senegal, USA, and Rwanda.